GLOBAL COMPETENCES AS AN EDUCATIONAL CHALLENGE: THE ROLE OF TEACHERS IN THE FACE OF PISA DEMANDS - Lyda Marcela Benavides Tamayo; Lihyna Plazas Arismendy; Yudy Alejandra Silva Manrique (LÍNEA IMAGINARIA, 2025)
Current educational systems face the challenge of preparing students for a rapidly changing and globalized world. Technological and informational advancements demand learners capable of engaging with this dynamic landscape, with teachers being the first called upon to understand it. This essay reflects on the global competencies assessed by the PISA standardized tests and their critical role in classroom integration. First, the paper provides a conceptual framework for global competencies and their significance in student development. It then presents an argumentative analysis highlighting the teacher’s pivotal role in implementing these competencies, examining both the strengths and challenges of this endeavor. Finally, it concludes by emphasizing the urgency of fostering these skills within the educational Colombian system.